Silver spoons and black mobility: The white South African economic elite and its implications for the upward mobility of blacks - P. Human; Linda Human (South African Journal of Business Management, 1987)
Implicit in any discussion of the concentration of economic power is the assumption that the South African economy is dominated by a coherent and cohesive white economic elite. Two separate but complementary perspectives can be used to explain this phenomenon. The classical social mobility perspective argues that elites in the western world have tended to reproduce themselves. By a process of 'social closure' which involves the use of two main exclusionary devices - property and credentials - groups attempt to optimize their own rewards by restricting access to resources and opportunities to 'insiders'. The related economic argument suggests that higher profit is achieved through a hegemonic kind of social organization which is sufficiently stable to facilitate the exchange of information and expertise between corporations, thus decreasing risk. The sociological and economic perspectives are analysed using data pertaining to South Africa's business elite. It is found that the sociological perspective is valid but that the economic perspective does not hold ground. The implications of exclusionary closure by the white business elite for both black mobility and the transfer of capital to black people are discussed.
Keywords: 650